2019
DOI: 10.1186/s12964-019-0331-9
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D/VDR signaling inhibits LPS-induced IFNγ and IL-1β in Oral epithelia by regulating hypoxia-inducible factor-1α signaling pathway

Abstract: Background Oral lichen planus (OLP) is known as a chronic inflammatory disease. Our recent studies have suggested that vitamin D/vitamin D receptor (VDR) signaling exerts its protective effects on oral keratinocyte apoptosis by regulating microRNA-802 and p53-upregulated modulator of apoptosis (PUMA), but its roles in oral epithelial inflammatory responses in OLP are still unknown. Herein, we identify lipopolysaccharide (LPS) is able to enhance interferon gamma (IFNγ) and interleukin-1 beta (IL-1β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 45 publications
(69 reference statements)
0
34
0
Order By: Relevance
“…Our choice of IL-1β as a marker of inflammation was based on reviews of literature reporting inflammatory markers in ASD [10,16,17], the impact of vitamin D and omega-3 LCPUFA on inflammatory markers [28,32,74], and the stability of the inflammatory markers in the blood [75]. It has been suggested that IL-1β is degraded within 2-3 years of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Our choice of IL-1β as a marker of inflammation was based on reviews of literature reporting inflammatory markers in ASD [10,16,17], the impact of vitamin D and omega-3 LCPUFA on inflammatory markers [28,32,74], and the stability of the inflammatory markers in the blood [75]. It has been suggested that IL-1β is degraded within 2-3 years of storage.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we focused on the mechanism of miR-27a/b reductions in OLP. www.nature.com/scientificreports www.nature.com/scientificreports/ Our recent data have indicated that vitamin D/VDR signaling plays a protective role in OLP by inhibiting cytokines secretion and apoptosis in oral keratinocytes 25,26 . In the current study, we located VDR binding sites in the promoter regions of miR-27a/b, implying vitamin D/VDR signaling possesses the potential of inducing miR-27a/b expression.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D or VDR overexpression has been proven to perform its regulatory functions in oral epithelium of OLP by impeding nuclear factor-κB (NF-κB) pathway or by inducing von Hippel-Lindau (VHL) 25,26 . In this work, we found that either VDR plasmids transfection or vitamin D treatment attenuated LPS or activated CD4 + T cell supernatant-induced miR-27a/b decreases in OLP cell models, proposing a notion that vitamin D/VDR signaling may control miR-27a/b expression to exert its physiological actions in OLP and expand the regulatory networks of vitamin D/VDR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that VD receptor (VDR) signaling has a protective effect on keratinocyte apoptosis in the oral cavity by regulating miRNA-802 and p53-positive apoptosis modulator (PUMA), which may be important when considering the pathogenesis of oral lichen planus (OLP) [5]. It was studied the molecular mechanisms of suppressing the expression of the in oral LP (OLP).…”
Section: Vitamin D and Cell Proliferation Differentiation And Apoptosismentioning
confidence: 99%
“…As a cytokine regulator, 1,25 (OH) 2D3 inhibited HIF-1α (hypoxia-induced factor-1α), which in turn blocked the production of IFNγ (interferon gamma) and IL-1β (interleukin-1 beta) in human oral keratinocytes. Given that in VDR -/ -mie, as well as in VDR-deficient human biopsies, the HIF-1α status of the oral epithelium is increased, which is accompanied by an increase in IFNγ and IL-1β, VD may play a role in the development of inflammation in OLP [5].…”
Section: Vitamin D Andinflammation and Immunitymentioning
confidence: 99%